Biological and physical contraints on maize production in the Humid Forest and Western Highlands of Cameroon - Ngoko, Z.; Cardwell, K.; Marasas, W.F.O.; Wingfield, M.; Ndemah, R.; Schulthess, F. (Springer, 2002)
The aim was to identify biological and physical factors responsible for reducing maize yield in Cameroon. Two surveys were conducted in 137 fields in two agroecological zones in 1995–1997. In the Humid Forest (HF), Bipolaris maydis, Stenocarpella macrospora, Puccinia polysora, Rhizoctonia solani and soil fertility were factors that reduced maize production in 1995 and 1996. In the Western Highlands (WHL), Cercospora zeae-maydis, and the interaction between soil fertility and maize variety were the most important constraints to maize production in 1996. In 1997, C. zeae-maydis, S. macrospora, physiological spot and stem borer damage (Busseola fusca) were negatively related to ear weight. The combination of these biological factors (diseases and insects), and the physical parameter of soil fertility were responsible for reducing maize yield in these selected benchmarks of Cameroon. Maximum potential yield reductions were estimated at 68% due to B. maydis and 46% due to S. macrospora, respectively, in the HF in 1995. In 1996, maximum potential yield reductions in the HF were estimated at 34%, 41% and 30% due to S. macrospora, P. polysora and R. solani, respectively. In the WHL, C. zeae-maydis had the potential to cause a yield reduction of 79% in 1996. In the WHL in 1997, the interaction between C. zeae-maydis and B. fusca, stem diseases and the physiological spot caused potential reductions of 52%, 34% and 39%, respectively.